Choices of Law for Democratic Regional Head Election Dispute Resolution Institutions in Indonesia - Amancik, Amancik; Ahmad Saifulloh, Putra Perdana; Ayub, Zainal Amin; Barus, Sonia Ivana; Ramadhani, Susi (Universitas Negeri Gorontalo, 2024)
This research aimed to provide a conceptual idea regarding legal options in resolving disputes of democratic regional head elections in Indonesia with two proposed options. The first option included revising the Election and Regional Election Law to grant authority to the Constitutional Court (MK) and Election Supervisory Agency (Bawaslu) for adjudicating disputes. The second option proposed implementing the Fifth Amendment to the 1945 Constitution to reconstruct the Constitutional Court as an election court correlating with the primary role of upholding regulations. These proposed options would grant the Constitutional Court the authority to examine and adjudicate substantial matters related to the constitutionality of elections. Furthermore, the analysis used normative legal research including statutory, comparative, and conceptual methods.